-(5-6x)=4(5x+6)

Simple and best practice solution for -(5-6x)=4(5x+6) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -(5-6x)=4(5x+6) equation:


Simplifying
-1(5 + -6x) = 4(5x + 6)
(5 * -1 + -6x * -1) = 4(5x + 6)
(-5 + 6x) = 4(5x + 6)

Reorder the terms:
-5 + 6x = 4(6 + 5x)
-5 + 6x = (6 * 4 + 5x * 4)
-5 + 6x = (24 + 20x)

Solving
-5 + 6x = 24 + 20x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-20x' to each side of the equation.
-5 + 6x + -20x = 24 + 20x + -20x

Combine like terms: 6x + -20x = -14x
-5 + -14x = 24 + 20x + -20x

Combine like terms: 20x + -20x = 0
-5 + -14x = 24 + 0
-5 + -14x = 24

Add '5' to each side of the equation.
-5 + 5 + -14x = 24 + 5

Combine like terms: -5 + 5 = 0
0 + -14x = 24 + 5
-14x = 24 + 5

Combine like terms: 24 + 5 = 29
-14x = 29

Divide each side by '-14'.
x = -2.071428571

Simplifying
x = -2.071428571

See similar equations:

| 3-(6-2x)=4 | | 7.5x+2=15.5x | | (12-8x)+(3x+12)=0 | | 21x+10=180 | | 4(w-6)=3(x+1) | | 8x+y=8fory | | s=2(3.14)rh+2(3.14)r^2 | | -x-4=0.6x+4 | | X^2-4x+6=o | | 4y-5x=3y-11+2x | | n=2k-7m-y | | x+y=133x-45y | | 2k+-7m-y=n | | 8xa=56 | | 7y^2-11y=6 | | 2k+-7m=n+y | | (X^3)-(1-i)=0 | | (10x)=-20 | | -5x+7x=5(-2x+24) | | 36n^2+9=73 | | 6x-24=100 | | 4p^2+8=44 | | 2(7)+p=35 | | 3y+x+5=y+12 | | 12-(4m+4)=2+2m-12 | | 4x^3+20x^2-x-5=0 | | 1+36r^2=50 | | 4y-5=y-11 | | (-3x+4)-(8x+4)= | | -1x^3-x^2+14x+168=0 | | y=3f | | 4a-4=8+c |

Equations solver categories